Morphology effect of ceria on the performance of CuO/CeO2 catalysts for hydrogen production by methanol steam reforming. (15th March 2019) - Yang, Shuqian; Zhou, Feng; Liu, Yujuan; Zhang, Lei; Chen, Yu; Wang, Honghao; Tian, Yuan; Zhang, Caishun; Liu, Daosheng
Abstract: Nano-rod(R), nano-particle(P) and sponginess(S) of ceria samples were used to study catalytic performance of hydrogen production by methanol steam reforming. The samples were prepared by hydrothermal method, precipitation method, and sol-gel method, respectively, and the CuO was supported on the different morpholopy of CeO2 samples by wet impregnation. SEM, TEM, XRD, XRF, BET, H2 -TPR, XPS and N2 O titration methods were used to study correlation between the structure and the catalytic performance for methanol steam reforming. The results showed that the morphology of the prepared CeO2 support dramatically influenced the performance of catalysts. Due to the stronger interaction between copper oxide and ceria support, the CuO/CeO2 -R catalyst had exhibited the better catalytic activity than those of the CuO/CeO2 P and CuO/CeO2 S catalysts. Moreover, higher Cu dispersion, lower reduction temperature of CuO, and higher content of active species Cu + were also advantageous to raising catalytic effects. Besides, with the highest content of surface Ce 3+, the CuO/CeO2 -R had estimated the content of oxygen vacancy on the surface of the catalyst. The existence of surface oxygen vacancy had a positive effect on the methanol steam reforming. Highlights: Ceria materials with different morphology were synthesized for methanol steam reforming. Effect of CeO2 morphology on the catalytic performance. Copper was doped on different morphologies of CeO2 by impregnation. Effect of interaction between copper and cerium on the catalytic performance. CuO/CeO2 -R (CeO2 nano-rod) catalyst showed high catalytic activity at low temperature for methanol steam reforming.